MOTIVASI TEMBANG PERTANIAN JAWA UNTUK TERWUJUDNYA KETAHANAN PANGAN NASIONAL - Purwadi Purwadi (Jurnal IKADBUDI, 2021)
This research on agricultural songs aims to achieve food security in the Javanese community. The spirit to plant fruit trees creates a safe and peaceful atmosphere. Agricultural songs were created in order to motivate farmers to work diligently in the fields. Abundant agricultural products are very beneficial to the community. Food security affects social order. The availability of food makes people calm at work.Keyword: song, agriculture, food security